PENGARUH KOMPETENSI DAN PERENCANAAN SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI UPTD PUSKESMAS LONG BELUAH KABUPATEN BULUNGAN - Palimbong, Jesita; Mujahid, Mujahid; Safar, Ilham (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
Therefore, this study aimed to analyze the effect of Human Resource Competency and Human Resource Planning on Employee Performance at the Long Beluah Community Health Center, Bulungan Regency. This study employed a quantitative research approach using a saturated sampling technique, involving all 49 employees. Data were collected through a structured questionnaire and analyzed using instrument validity and reliability tests, multiple linear regression analysis, partial t-tests, simultaneous F-tests, and the coefficient of determination (R²). The findings indicated that all questionnaire items were valid and reliable. The partial t-tests revealed that both Human Resource Competency and Human Resource Planning individually had a positive and statistically significant effect on Employee Performance. The simultaneous F-test also confirmed that Human Resource Competency and Human Resource Planning jointly exerted a positive and significant influence on Employee Performance. The coefficient of determination (R²) showed that Human Resource Competency and Human Resource Planning collectively explained 73.6% of the variance in Employee Performance. These findings indicate that improving employees' competencies and implementing effective human resource planning can significantly enhance employee performance at the Long Beluah Community Health Center.